Allen Squires, Edna Tucker, and Jake Tucker in front of house. - Squires, Allen; Squires, Pearl (1962)
Photograph of Allen Squires, his sister Edna and her husband Jake in front of the Tucker's house. Identified by Pearl Squires on slide label.